Design, evaluation, cytotoxic activity, molecular docking, ADMET analysis, and dynamic simulations and the preparation of new isoxazoles, thiazoles, 1,3-thiazines, and thiazolopyrimidines derived from quinoline-pyridopyrimidines - Ameen A. Abu-Hashem; Nasser Amri; Ahmed F. El-Sayed (Pharmaceutical Biology)
Context Quinoline, isoxazole, and pyridothiazolopyrimidinone derivatives are novel compounds with significant biological activity, exhibiting anticancer properties and holding promising therapeutic applications.Objective This investigation synthesized new heterocyclic compounds in high yields from quinoline-2-thioxo-pyridopyrimidinone and assessed their anticancer activities. Additionally, it conducted molecular docking, ADMET analysis, and molecular dynamics simulations.Materials and methods A new series of quinoline-pyridothiazolopyrimidine derivatives has been synthesized using advanced techniques. The structures of the new compounds were confirmed using IR, NMR, MS and elemental analysis. All compounds were tested in vitro for their anticancer activity.Results Isoxazole and thiazolopyridopyrimidinones displayed the highest activity against several cancer cell lines. Docking simulations revealed that compounds 5d, 5e, 11a, and 11b exhibited favorable binding energies and effectively interacted with the active sites of the EGFR, CDK2, ERα, and VEGFR receptors. The ADMET analysis of these compounds demonstrated compliance with Pfizer’s rules. Molecular dynamics simulations confirmed the stability of complexes formed by compounds 5d, 11a, and 11b with CDK2, ERα, VEGFR, and EGFR. The root mean square deviation (RMSD) values were recorded, while the root mean square fluctuation (RMSF) values ranged from 0.10 to 0.6 nm. The solvent-accessible surface area (SASA) values were measured to be between 135–145 nm2, 125–130 nm2, 155–165 nm2, and 160–175 nm2.Discussion and conclusions The cytotoxicity (IC50) and selectivity index are presented in Tables. Molecular docking analyses showed that compounds 5d, 5e, 11a, and 11b demonstrated significant binding energies. These consistent results support the notion that both practical and theoretical studies align regarding the anticancer properties of these new compounds. Furthermore, these findings emphasize the potential of these compounds in ongoing drug development efforts.